2014
DOI: 10.9790/0853-13155366
|View full text |Cite
|
Sign up to set email alerts
|

Management of Dental Waste in Private Clinics in Chhattisgarh State, India – A Cross Sectional Study

Abstract: Aims: Dentistry is a profession dedicated to promoting and enhancing oral health and well-being. To accomplish these goals, dentists use a variety of materials and equipment. Unfortunately, some of the materials that are currently in use like silver amalgam, x-ray films etc. including heavy metals and biomedical waste present potential challenges to the environment. Hence the aim of the present study was to assess the management of dental waste in private clinics of Chhattisgarh state, India. Methods and Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
4
1
1
Order By: Relevance
“…A self-administered questionnaire was used in our study as it allows us to gather large amount of data quickly and economically. Our study had 614 participants, which was higher than those of Arora et al 16 and…”
Section: Discussioncontrasting
confidence: 42%
“…A self-administered questionnaire was used in our study as it allows us to gather large amount of data quickly and economically. Our study had 614 participants, which was higher than those of Arora et al 16 and…”
Section: Discussioncontrasting
confidence: 42%
“…A study in India reported that 79% of the respondents disposed of their generated amalgam waste together with general waste, while 13% of them disposed of this waste in other inappropriate ways. 12 In a facility-based study in Iran, it was found that 92% of the facilities disposed of amalgam waste in toilets as well as the sewer system. 22 A study done in Palestine found that over 80% of generated amalgam waste was disposed of into either the clinic garbage or drain.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, Asian and middle-east, it has been noted in previous reports that medical waste is poorly sorted, characterized and disposed, further highlighting its pertinence in the health system framework. 11,12,13 In underdeveloped nations, the difficulties in managing the waste from dental facilities are especially apparent. 14,15 Managing dental waste according to accepted norms is much more difficult in developing nations due to limited resources resulting in an increase in health risks and environmental contamination from the improper management, storage, transportation, and disposal of clinical waste.…”
Section: Open Access Research Articlementioning
confidence: 99%
“…[ 22 ] Amalgam separator use was low among participants of studies conducted in Uttar Pradesh, Karnataka and Chhattisgarh. [ 3 19 20 21 ] In some studies, paramedical staffs were also included which showed that there was lacunae in awareness and practice of BMW management among these staff. [ 2 18 , 21 ]…”
Section: Discussionmentioning
confidence: 99%